Postmodern elements in Mohja Kahf’s the girl in the tangerine scarf and Mohsin Hamid’s the reluctant fundamentalist - Abdullah, Suhaila; Quayum, Mohammad Abdul (translator) (IIUM Press, International Islamic University Malaysia, 2017)
This qualitative research studies postmodernism, postmodern culture and the postmodern mind in two novels written by diasporic Muslim writers: Mohja Kahf’s The Girl in the Tangerine Scarf (2009) and Mohsin Hamid’s The Reluctant Fundamentalist (2007). By focusing on postmodern elements, this book investigates the lives of immigrants who came from South Asia and Syria, as well as the major challenges these immigrants encounter in adapting to American culture. Immigrants face problems such as a yearning for home, trying to find a sense of belonging in a new land and a sense of displacement. However, this study would like to add to the discussion that not only do the immigrants in the novels face these problems but they are also confronted by additional challenges while trying to navigate postmodern American culture. This study attempts to understand the hurdles that immigrants face due to postmodernism and to study the ways in which they are attempting to survive a culture that promotes constant changes and instability. This book also explores how postmodern culture affects the thoughts of individuals who live in the age of postmodernism by trying to understand the postmodern mind. In addition, this book analyses how postmodern ideals influence social relationships between the immigrants and Americans in the novels. A thorough analysis of two texts reveals that the authors acknowledge the differences of Arab and Pakistani cultures in comparison to postmodern American culture.